1984
DOI: 10.1007/bf01321321
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual, methodological, and clinical issues in the assessment of anxiety disorders

Abstract: Issues Many conceptual, methodological, and clinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Each of these domains is suggested to measure a separate element of response characteristics and potentially independent underlying mechanisms to the construct of anxiety [3]. An influential model of anxiety sees it as reflecting the engagement of the Behavioural Inhibition System (BIS) of which the hippocampus is a key component [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these domains is suggested to measure a separate element of response characteristics and potentially independent underlying mechanisms to the construct of anxiety [3]. An influential model of anxiety sees it as reflecting the engagement of the Behavioural Inhibition System (BIS) of which the hippocampus is a key component [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lang’s tripartite model of anxiety suggests that it consists of three response domains: cognitive, behavioural, and physiological [ 1 ], which together result in a state of apprehensive worry, hyperarousal to threat cues, avoidance behaviours and negatively-biased cognitions [ 2 ]. Each of these domains is suggested to measure a separate element of response characteristics and potentially independent underlying mechanisms to the construct of anxiety [ 3 ]. An influential model of anxiety sees it as reflecting the engagement of the Behavioural Inhibition System (BIS) of which the hippocampus is a key component [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with high trait anxiety may remain chronically in a generalized state of anxiety. They are more likely to develop clinical anxiety (29, 30), more vulnerable to stress and respond to a wider range of situations as dangerous or threatening (28). Trait anxiety has also been shown to affect the effectiveness of intervention procedures in other areas of anxiety research (31).…”
mentioning
confidence: 99%
“…Among the changes was the creation of two subgroups (anxiety states and phobias) and a distinct panic disorder category within the anxiety state subgroup. Recent reports have revealed that there is considerable overlap of symptoms among the anxiety disorders (e.g., Spitzer, 1985; Turner & Michelson, 1984). Moreover, the presence of one anxiety symptom is associated with an increased likelihood of another.…”
mentioning
confidence: 99%